2017
DOI: 10.1111/eea.12615
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual competitiveness of two Ceratitis capitata strains, tsl Vienna 8 and OX3864A transgenics, in field cage conditions

Abstract: The success of the sterile insect technique (SIT) depends on the ability of sterile males to compete effectively with wild males to mate with wild females. This study compared the sexual competitiveness and other behavioral parameters of males of two strains of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), tsl Vienna 8 (tsl V-8) and the transgenic line OX3864A, in competition with wild males from the São Francisco Valley region in Bahia, Brazil. Mating events were observed in field cages containing vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our data showed that male condition did not influence mating latency period; however, sterile females presented a longer mating latency compared to fertile females. Effects of irradiation on latency were previously reported in males of B. cucurbitae, B. tryoni and C. capitata, but not in females (Haq et al, 2013;Radhakrishnan et al, 2009;Virginio et al, 2017). According to Cayol, Vilardi, Rial, and Vera (1999), mating latency is controlled by females and not by males.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our data showed that male condition did not influence mating latency period; however, sterile females presented a longer mating latency compared to fertile females. Effects of irradiation on latency were previously reported in males of B. cucurbitae, B. tryoni and C. capitata, but not in females (Haq et al, 2013;Radhakrishnan et al, 2009;Virginio et al, 2017). According to Cayol, Vilardi, Rial, and Vera (1999), mating latency is controlled by females and not by males.…”
Section: Discussionmentioning
confidence: 90%
“…The female condition of D. suzukii did not have an effect on mating duration, but sterile males differ from fertile males in the duration of copula. Shorter copulation when sterile males are involved was already reported for A. serpentina, A. fraterculus and C. capitata (Allinghi et al, 2007;Cayol et al, 1999;Landeta-Escamilla et al, 2016;Virginio et al, 2017). Nonetheless, the importance of this effect on the efficiency of the SIT is not clear, since there is no relationship between copulation duration and the ability of males to transfer sperm (Allinghi et al, 2007;Collins et al, 2012;Harmer, Radhakrishnan, & Taylor, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…A much higher value of RSI (0.80 ± 0.11) demonstrated that the Salaya1 sterile males can succeed more often in the mating competition with the wild females when they were irradiated at 50 Gy. This RSI value is unusally high when compared with the values from GSSs Vienna 8 (0.22 to 0.34) [ 38 , 39 ] and Tapachula-7 (0.4) [ 40 ]. However, this is consistent with a previous finding.…”
Section: Discussionmentioning
confidence: 96%
“…Virginio et al. () compared the mating performances of an established medfly strain with a new, transgenic strain in field cage experiments. No differences between the two SIT strains were found, although wild males consistently outperformed males of both SIT strains.…”
mentioning
confidence: 99%
“…Augustinos et al (2017) compared two medfly genetic sexing strains in laboratory experiments, and report differences in egg hatch, pupation, and emergence rates, and in male tolerance to elevated temperatures. Virginio et al (2017) compared the mating performances of an established medfly strain with a new, transgenic strain in field cage experiments. No differences between the two SIT strains were found, although wild males consistently outperformed males of both SIT strains.…”
mentioning
confidence: 99%